Heat storage structure and method for producing the same
A heat storage structure combining chemical materials with fibrous carbon nanostructures addresses durability issues by forming a flexible matrix, achieving superior heat storage and durability through controlled volume changes.
Patent Information
- Application Number
- JP2023108531
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2025-01-17
AI Technical Summary
Heat storage structures using chemical heat storage materials face issues with durability due to volume changes during heat storage and dissipation, leading to damage and poor performance.
A heat storage structure comprising a chemical heat storage material and fibrous carbon nanostructures with specific properties, including a BET specific surface area of 600 m²/g or more and a mass ratio of 1 to 20, forms a strong matrix that withstands volume changes, enhancing durability and heat storage performance.
The structure achieves excellent heat storage properties and durability by utilizing fibrous carbon nanostructures to form a flexible matrix that absorbs volume changes, ensuring high reactivity and initial heat dissipation characteristics.
Smart Images

Figure 2025007255000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a heat storage structure and a method for manufacturing a heat storage structure. [Background technology]
[0002] 2. Description of the Related Art In recent years, technology relating to a heat storage structure using a chemical heat storage material that stores heat through a chemical reaction has been considered as a highly efficient heat storage technology.
[0003] For example, Patent Document 1 reports that a chemical heat storage material containing hydroxide and / or oxide of calcium and / or magnesium, hydroxide of lithium, and chloride of lithium has a high reaction rate and is capable of storing heat at low temperatures. According to Patent Document 1, the chemical heat storage material can be used as a molded body by performing press molding or the like. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2019 / 159791 Summary of the Invention [Problem to be solved by the invention]
[0005] However, the heat storage structure obtained by molding the heat storage material using the method of Patent Document 1 has poor durability and has the problem of being damaged during molding or due to volumetric changes in the chemical heat storage material accompanying heat storage and release.
[0006] Therefore, an object of the present invention is to provide a heat storage structure that exhibits sufficient heat storage capacity while also being excellent in durability, and a method for manufacturing the same. [Means for solving the problem]
[0007] The present inventors have conducted extensive research to achieve the above object, and have newly discovered that a heat storage structure containing a chemical heat storage material and a fibrous carbon nanostructure having a predetermined property, and in which the mass ratio between them is within a predetermined range, has excellent heat storage properties and durability, and have completed the present invention.
[0008] That is, an object of the present invention is to advantageously solve the above problems, and the present invention provides the following heat storage structures [1] to [4] and manufacturing methods for the heat storage structures [5] to [6].
[0009] [1] A chemical heat storage material and a fibrous carbon nanostructure, the fibrous carbon nanostructure having a BET specific surface area of 600 m 2 / g or more, and the ratio of the mass of the chemical heat storage material to the mass of the fibrous carbon nanostructure is 1 or more and 20 or less. A heat storage structure containing a chemical heat storage material and a fibrous carbon nanostructure having a BET specific surface area of the above value or more in the above mass ratio has excellent heat storage properties and durability.
[0010] In this specification, the term "fibrous carbon nanostructure" refers to a fibrous carbon structure having an outer diameter (fiber diameter) of less than 1 μm. In this specification, the term "BET specific surface area" refers to a nitrogen adsorption specific surface area measured using the BET (Brunauer-Emmett-Teller) method. In this specification, the "mass of the chemical heat storage material" refers to the mass of the chemical heat storage material, which can be in a heat storage state and a heat release state, in the heat storage state.
[0011] [2] The heat storage structure according to [1] above, wherein the chemical heat storage material includes at least one selected from the group consisting of magnesium hydroxide heat storage material, calcium hydroxide heat storage material, calcium carbonate heat storage material, barium hydroxide heat storage material, and Li4SiO4 heat storage material. If the chemical heat storage material is any of those described above, the heat storage capacity of the heat storage structure can be further improved.
[0012] In this specification, the term "magnesium hydroxide heat storage material" refers to a chemical heat storage material that becomes magnesium oxide (MgO) in a heat storage state and becomes magnesium hydroxide (Mg(OH)2) in a heat release state. In this specification, the term "calcium hydroxide heat storage material" refers to a chemical heat storage material that becomes calcium oxide (CaO) in a heat storage state and becomes calcium hydroxide (Ca(OH)2) in a heat release state. In this specification, the term "calcium carbonate heat storage material" refers to a chemical heat storage material that becomes calcium oxide (CaO) in a heat storage state and becomes calcium carbonate (CaCO3) in a heat release state. In this specification, the term "barium hydroxide heat storage material" refers to a chemical heat storage material that becomes barium oxide (BaO) in a heat storage state and barium hydroxide (Ba(OH)2) in a heat release state. In this specification, the term "Li4SiO4 heat storage material" refers to a chemical heat storage material that becomes Li4SiO4 in a heat storage state and Li2SiO3 and Li2CO3 in a heat release state.
[0013] [3] The heat storage structure according to [1] or [2] above, wherein the maximum bundle diameter of the fibrous carbon nanostructure is 0.2 μm or more and 0.9 μm or less. When the maximum bundle diameter of the fibrous carbon nanostructure is within the above-mentioned range, the durability of the heat storage structure can be further improved.
[0014] In this specification, the "maximum bundle diameter" of the fibrous carbon nanostructure can be measured by the method described in the Examples.
[0015] [4] Specific gravity is 0.25g / cm 3 More than 0.95g / cm 3 The heat storage structure according to any one of the above items [1] to [3], which is as follows: If the specific gravity is within the above range, the heat storage property of the heat storage structure can be further improved while the durability can be further increased. In addition, the reactivity of the chemical heat storage material can be increased, and the initial heat dissipation characteristic of the heat storage structure can be improved.
[0016] In this specification, the "specific gravity" of a heat storage structure is defined as the ratio of the mass (g) of the heat storage structure to the volume (cm3 ) can be calculated by dividing it by
[0017] [5] BET specific surface area is 600m 2 1. A method for manufacturing a heat storage structure, comprising: a dispersing step of dispersing fibrous carbon nanostructures having a particle diameter of 15 μm or more and 50 μm or less in a dispersion medium to prepare a dispersion liquid in which the dispersed particle diameter of the fibrous carbon nanostructures is 15 μm or more and 50 μm or less; a mixing step of mixing the dispersion liquid with a chemical heat storage material so that the ratio of the mass of the chemical heat storage material to the mass of the fibrous carbon nanostructures in the dispersion liquid is 1 or more and 20 or less to prepare a mixed liquid; and a forming step of removing the dispersion medium from the mixed liquid to obtain the heat storage structure. By employing the above-mentioned procedure, a heat storage structure having excellent heat storage capacity and durability can be produced.
[0018] In this specification, the "dispersed particle size" of the fibrous carbon nanostructure in the dispersion liquid can be measured by the method described in the Examples.
[0019] [6] The method for producing a heat storage structure according to [5] above, wherein the chemical heat storage material includes at least one selected from the group consisting of magnesium hydroxide heat storage material, calcium hydroxide heat storage material, calcium carbonate heat storage material, barium hydroxide heat storage material, and Li4SiO4 heat storage material. If the chemical heat storage material is any of those described above, the heat storage capacity of the heat storage structure can be further improved. Effect of the Invention
[0020] According to the present invention, it is possible to provide a heat storage structure that exhibits sufficient heat storage capacity while also having excellent durability, and a method for manufacturing the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] Hereinafter, an embodiment of the present invention will be described in detail.
[0022] (heat storage structure) The heat storage structure of the present invention is a molded body containing a chemical heat storage material and a fibrous carbon nanostructure. The heat storage structure of the present invention can have any shape depending on its application, and can be, for example, a sheet shape, a cylindrical shape, or a rectangular parallelepiped shape. In addition, the heat storage structure of the present invention may contain components other than the chemical heat storage material and the fibrous carbon nanostructure (hereinafter, sometimes referred to as "other components"). In the heat storage structure of the present invention, the BET specific surface area of the fibrous carbon nanostructure is 600 m 2 / g or more, and the ratio of the mass of the chemical heat storage material to the mass of the fibrous carbon nanostructure (hereinafter sometimes referred to as the "mass ratio of chemical heat storage material / fibrous carbon nanostructure") is 1 or more and 20 or less, so that it has both excellent heat storage properties and durability.
[0023] The reason why the heat storage structure of the present invention has excellent heat storage properties and durability is presumed to be as follows. First, the fibrous carbon nanostructure contained in the heat storage structure of the present invention has a BET specific surface area of 600 m 2 / g or more, a strong matrix is formed by the fibrous carbon nanostructure. This matrix forms a structure in which the fibrous carbon nanostructure is entangled, and has the flexibility to fully absorb volume changes, for example, even if a volume change occurs in the chemical heat storage material. In addition, since the heat storage structure of the present invention has a mass ratio of chemical heat storage material / fibrous carbon nanostructure of 20 or less, the amount of fibrous carbon nanostructure for forming the matrix is sufficient, and excellent durability can be exhibited. Furthermore, since the mass ratio is 1 or more, the amount of chemical heat storage material is also secured, and it is considered that the heat storage structure can exhibit good heat storage properties.
[0024] <Chemical heat storage material> The chemical heat storage material is an inorganic compound that can store and release heat by utilizing the heat of chemical reaction that occurs when it comes into contact with a reactive medium such as water or carbon dioxide.
[0025] As the chemical heat storage material, from the viewpoint of further improving the heat storage property of the heat storage structure, magnesium hydroxide heat storage material, calcium hydroxide heat storage material, calcium carbonate heat storage material, barium hydroxide heat storage material, and Li4SiO4 heat storage material are preferably mentioned, magnesium hydroxide heat storage material, calcium hydroxide heat storage material, and barium hydroxide heat storage material are more preferable, and magnesium hydroxide heat storage material is particularly preferable. The chemical heat storage material may be used alone or in combination of two or more kinds.
[0026] In addition, the mass of the chemical heat storage material contained in the heat storage structure is preferably 60% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, particularly preferably 90% by mass or more, and preferably 95% by mass or less, more preferably 94% by mass or less, and even more preferably 93% by mass or less, based on the total mass of the heat storage structure being 100% by mass. If the proportion of the chemical heat storage material in the heat storage structure is 60% by mass or more, the heat storage property of the heat storage structure can be further improved and the initial heat dissipation characteristics can be enhanced. On the other hand, if the proportion of the chemical heat storage material in the heat storage structure is 95% by mass or less, the durability of the heat storage structure can be further improved. In this specification, the "total mass of the heat storage structure" refers to the total mass calculated as the mass of the chemical heat storage material in a heat stored state.
[0027] <Fibrous carbon nanostructures> As the fibrous carbon nanostructure, for example, a cylindrical carbon nanostructure such as a carbon nanotube (hereinafter sometimes referred to as "CNT"), or a non-cylindrical carbon nanostructure such as a carbon nanostructure in which a 6-membered carbon ring network is formed in a flattened cylinder can be used. These may be used alone or in combination of two or more.
[0028] Among the above, as the fibrous carbon nanostructure, it is preferable to use a fibrous carbon nanostructure containing CNT, from the viewpoint of further improving the heat storage capacity of the heat storage structure while further increasing its durability.
[0029] Here, the fibrous carbon nanostructure containing CNT may be composed only of CNT, or may be a mixture of CNT and a fibrous carbon nanostructure other than CNT. The CNTs in the fibrous carbon nanostructure are not particularly limited, and single-walled carbon nanotubes and / or multi-walled carbon nanotubes can be used. However, from the viewpoint of further improving the heat storage capacity of the heat storage structure while further enhancing its durability, the CNTs are preferably single-walled to five-walled carbon nanotubes, and more preferably single-walled carbon nanotubes.
[0030] In addition, the fibrous carbon nanostructure containing CNT can be produced by using known CNT synthesis methods such as arc discharge, laser ablation, and chemical vapor deposition (CVD), without any particular limitation. Specifically, the fibrous carbon nanostructure containing CNT can be efficiently produced in accordance with a method (super growth method; see International Publication No. 2006 / 011655) in which, for example, a raw material compound and a carrier gas are supplied onto a substrate having a catalyst layer for producing carbon nanotubes on its surface, and a trace amount of an oxidizing agent (catalyst activation material) is made present in the system when synthesizing CNT by chemical vapor deposition (CVD), thereby dramatically improving the catalytic activity of the catalyst layer. In the following, the carbon nanotubes obtained by the super growth method may be referred to as "SGCNT". Furthermore, the fibrous carbon nanostructure containing CNTs produced by the super-growth method may be composed only of SGCNTs, or may contain, in addition to SGCNTs, other carbon nanostructures, such as non-cylindrical carbon nanostructures.
[0031] Here, the fibrous carbon nanostructure has a BET specific surface area of 600 m as described above. 2 / g or more, and 700m 2 / g or more, and 2 / g or more is more preferable, and 2 / g or more is more preferable, 2 / g or more is particularly preferable, and 2500m 2 / g or less, and 2 It is more preferable that the BET specific surface area of the fibrous carbon nanostructure is 600 m 2 When the BET specific surface area of the fibrous carbon nanostructure is less than 2500 m / g, a heat storage structure having excellent durability cannot be obtained as a molded body. 2 If the carbon nanostructure has a molecular weight of 1000 or less, aggregation of the fibrous carbon nanostructure can be suppressed, making it possible to prepare a heat storage structure that is homogeneous and has even greater durability.
[0032] In addition, the average diameter of the fibrous carbon nanostructure is preferably 0.5 nm or more, more preferably 1 nm or more, and is preferably 15 nm or less, more preferably 10 nm or less. If the average diameter of the fibrous carbon nanostructure is within the above-mentioned range, the heat storage property of the heat storage structure can be further improved, and the durability can be further increased. In this specification, the average diameter of the fibrous carbon nanostructures can be determined by measuring the diameter (outer diameter) of 100 randomly selected fibrous carbon nanostructures using a transmission electron microscope. The average diameter of the fibrous carbon nanostructures may be adjusted by changing the manufacturing method or manufacturing conditions of the fibrous carbon nanostructures, or by combining multiple types of fibrous carbon nanostructures obtained by different manufacturing methods.
[0033] In the heat storage structure of the present invention, at least some of the fibrous carbon nanostructures may be aggregated to form a bundle. The maximum bundle diameter of the fibrous carbon nanostructures is preferably 0.2 μm or more, more preferably 0.3 μm or more, even more preferably 0.4 μm or more, preferably 0.9 μm or less, more preferably 0.8 μm or less, and even more preferably 0.7 μm or less. If the maximum bundle diameter of the fibrous carbon nanostructures is within the above-mentioned range, the heat storage property of the heat storage structure can be further improved while the durability can be further increased. The maximum bundle diameter of the fibrous carbon nanostructures can be adjusted by changing the average diameter of the fibrous carbon nanostructures or the manufacturing conditions of the heat storage structure.
[0034] Furthermore, the mass of the fibrous carbon nanostructure contained in the heat storage structure is preferably 5% by mass or more, more preferably 6% by mass or more, even more preferably 7% by mass or more, preferably 40% by mass or less, more preferably 30% by mass or less, even more preferably 20% by mass or less, and particularly preferably 10% by mass or less, based on the total mass of the heat storage structure being 100% by mass. If the proportion of the fibrous carbon nanostructure in the heat storage structure is 5% by mass or more, the durability of the heat storage structure can be further increased, and if it is 40% by mass or less, the heat storage property of the heat storage structure can be further improved.
[0035] <Other ingredients> Other components that may be optionally contained in the heat storage structure of the present invention are not particularly limited, and include known additives such as dispersants used during preparation of the heat storage structure. The heat storage structure preferably does not substantially contain additives such as dispersants, and is composed only of a chemical heat storage material and a fibrous carbon nanostructure. Here, "substantially does not contain additives" refers to the absence of additives other than those that inevitably remain in the heat storage structure due to manufacturing problems.
[0036] <Mass ratio of chemical heat storage material / fibrous carbon nanostructure> In the heat storage structure of the present invention, the mass ratio of the chemical heat storage material / fibrous carbon nanostructure must be 1 or more and 20 or less, as described above, and is preferably 3 or more, more preferably 6 or more, even more preferably 9 or more, preferably 18 or less, more preferably 16 or less, and even more preferably 14 or less. If the mass ratio of the chemical heat storage material / fibrous carbon nanostructure is less than 1, the heat storage property of the heat storage structure decreases, and if it exceeds 20, the durability of the heat storage structure is impaired.
[0037] <Specific gravity> The heat storage structure of the present invention has a specific gravity of 0.25 g / cm 3 It is preferable that the content is 0.3 g / cm or more. 3 More preferably, it is 0.4 g / cm or more. 3 More preferably, it is 0.95 g / cm or more. 3 It is preferable that the density is 0.85 g / cm or less. 3 More preferably, it is 0.75 g / cm or less. 3 More preferably, the specific gravity is 0.25 g / cm or less. 3 If the specific gravity is 0.95 g / cm or more, the durability of the heat storage structure can be further improved. 3 If the carbon nanostructure has a fibrous structure, the voids in the matrix are sufficiently secured, and the reactivity of the chemical heat storage material is enhanced. This is presumably the reason why the heat storage capacity of the heat storage structure is further improved, and the initial heat dissipation characteristics are also improved.
[0038] (Method of manufacturing heat storage structure) The method for producing a heat storage structure of the present invention can be used to produce the heat storage structure described above. The method for producing a heat storage structure of the present invention is a method for producing a heat storage structure having a BET specific surface area of 600 m 2 The method includes a dispersing step of dispersing fibrous carbon nanostructures having a particle size of 15 μm or more and 50 μm or less in a dispersion medium to prepare a dispersion liquid in which the dispersed particle size of the fibrous carbon nanostructures is 15 μm or more and 50 μm or less, a mixing step of mixing the dispersion liquid obtained in the dispersing step with a chemical heat storage material so that the ratio of the mass of the chemical heat storage material to the mass of the fibrous carbon nanostructures in the dispersion liquid is 1 to 20 to prepare a mixed liquid, and a forming step of removing the dispersion medium from the mixed liquid obtained in the mixing step to obtain a heat storage structure. Note that the method for producing the heat storage structure of the present invention is not particularly limited as long as it can produce a heat storage structure, and may include steps other than the dispersing step, the mixing step, and the forming step. The heat storage structure obtained by using the method for manufacturing a heat storage structure of the present invention has excellent heat storage properties and durability.
[0039] <Dispersion process> In the dispersion step, a dispersion liquid in which the fibrous carbon nanostructures are dispersed in a dispersion medium is prepared. The dispersion liquid may contain other components such as the dispersant described above in the section on "heat storage structure."
[0040] <<Fibrous carbon nanostructures>> As for the fibrous carbon nanostructure, the BET specific surface area mentioned in the “Heat storage structure” section is 600 m. 2 The preferred ranges of the BET specific surface area and average diameter of the fibrous carbon nanostructure used in the preparation of the dispersion are the same as those of the fibrous carbon nanostructure constituting the heat storage structure.
[0041] Here, the average length of the fibrous carbon nanostructures used in preparing the dispersion liquid is preferably 1 μm or more, more preferably 100 μm or more, and is preferably 5000 μm or less, more preferably 3000 μm or less, and even more preferably 1000 μm or less. If the average length of the fibrous carbon nanostructures is within the above-mentioned range, the dispersed particle size of the fibrous carbon nanostructures described later can be easily controlled to a desired range, and the heat storage property and durability of the obtained heat storage structure can be further improved. In this specification, the average length of the fibrous carbon nanostructures can be determined by measuring the lengths of 100 randomly selected fibrous carbon nanostructures using a transmission electron microscope.
[0042] <<Dispersion medium>> The dispersion medium is not particularly limited, and examples thereof include water, methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, t-butanol, pentanol, hexanol, heptanol, octanol, nonanol, decanol, and amyl alcohol, ketones such as acetone, methyl ethyl ketone, and cyclohexanone, esters such as ethyl acetate and butyl acetate, ethers such as diethyl ether, dioxane, and tetrahydrofuran, amide polar organic solvents such as N,N-dimethylformamide and N-methylpyrrolidone, and aromatic hydrocarbons such as toluene, xylene, chlorobenzene, orthodichlorobenzene, and paradichlorobenzene. These may be used alone or in combination of two or more. Among these, water and methyl ethyl ketone are preferable as the dispersion medium.
[0043] <<Dispersed particle size>> The dispersion liquid prepared in the dispersion step needs to have a dispersed particle diameter of the fibrous carbon nanostructure of 15 μm or more and 50 μm or less as described above, preferably 17 μm or more, more preferably 19 μm or more, preferably 45 μm or less, more preferably 40 μm or less, even more preferably 35 μm or less, and particularly preferably 30 μm or less. If the dispersed particle diameter of the fibrous carbon nanostructure is less than 15 μm, the durability of the heat storage structure cannot be ensured, and in some cases, it may be difficult to form the heat storage structure. On the other hand, if the dispersed particle diameter of the fibrous carbon nanostructure exceeds 50 μm, it is presumed that this is because it becomes difficult to temporarily fix the chemical heat storage material by the fibrous carbon nanostructure in the mixed liquid described later, but when the mixed liquid is filtered, the chemical heat storage material settles early, the porous substrate becomes clogged, and the dispersion medium becomes difficult to remove.
[0044] <<Distributed processing>> The dispersion liquid in which the dispersed particle size of the fibrous carbon nanostructure is within the above-mentioned range is not particularly limited, but is preferably prepared by a dispersion treatment that produces a cavitation effect or a disintegration effect. The dispersion treatment that produces a cavitation effect is a dispersion method that utilizes shock waves generated by the bursting of vacuum bubbles generated in a liquid when high energy is applied to the liquid. Specific examples of the dispersion treatment that produces a cavitation effect include a dispersion treatment using an ultrasonic homogenizer, a dispersion treatment using a jet mill, and a dispersion treatment using a high shear stirrer. The dispersion treatment that produces a disintegration effect is a dispersion method in which a shear force is applied to a composition (crude dispersion liquid) containing fibrous carbon nanostructures and a dispersion medium to disintegrate and disperse aggregates of the fibrous carbon nanostructures, and a back pressure is applied to the crude dispersion liquid to suppress the generation of bubbles, thereby uniformly dispersing the fibrous carbon nanostructures in the dispersion medium. The dispersion treatment that produces a disintegration effect can be performed using a commercially available dispersion system (for example, the product name "BERYU SYSTEM PRO" (manufactured by Biryu Co., Ltd.).
[0045] Among these, the preferred dispersion treatment for preparing the fibrous carbon nanostructure dispersion is one in which a dispersion treatment device equipped with a capillary flow path is used, and a coarse dispersion is pumped through the capillary flow path to apply shear force to the coarse dispersion to disperse the fibrous carbon nanostructures. By pumping the coarse dispersion through the capillary flow path to apply shear force to the coarse dispersion to disperse the fibrous carbon nanostructures, the fibrous carbon nanostructures can be well dispersed while suppressing damage to the fibrous carbon nanostructures, and the dispersed particle size of the fibrous carbon nanostructures can be easily controlled within a desired range.
[0046] Here, examples of dispersion processing devices equipped with a capillary flow path include wet jet mills (e.g., product names "JN5", "JN10", "JN20", "JN100", "JN1000" (all manufactured by Tokoh Co., Ltd.)) and the above-mentioned dispersion system (manufactured by Biryu Co., Ltd., product name "BERYU SYSTEM PRO").
[0047] The capillary flow path of the dispersion processing device may be a single capillary flow path, or may be a plurality of capillary flow paths having a junction at any downstream position. However, from the viewpoint of more effectively colliding the coarse dispersion liquids with each other to impart shear force and easily control the dispersed particle size of the fibrous carbon nanostructures within a desired range, it is preferable that the capillary flow path of the dispersion processing device is a plurality of capillary flow paths having a junction at any downstream position.
[0048] Furthermore, the diameter of the capillary flow path of the dispersion treatment device is not particularly limited, but from the viewpoint of effectively applying high-speed flow shear to the coarse dispersion without clogging the coarse dispersion and easily controlling the dispersed particle size of the fibrous carbon nanostructures within the desired range, it is preferably 50 μm or more and 1000 μm or less, and more preferably 50 μm or more and 600 μm or less.
[0049] The means for pressure-feeding the crude dispersion to the thin tube flow path is not particularly limited, and a high-pressure pump or a cylinder having a piston structure can be used.
[0050] The pressure at which the crude dispersion is pumped through the capillary flow path is not particularly limited, but is preferably 60 MPa or more and 200 MPa or less. If the pressure at which the crude dispersion is pumped through the capillary flow path is within the above range, the fibrous carbon nanostructures can be well dispersed while sufficiently suppressing the occurrence of damage to the fibrous carbon nanostructures, and the dispersed particle size of the fibrous carbon nanostructures can be easily controlled within a desired range.
[0051] <Mixing process> In the mixing step, the dispersion liquid obtained in the dispersion step and the chemical heat storage material are mixed to prepare a mixed liquid containing the fibrous carbon nanostructure, the chemical heat storage material, and the dispersion medium. The mixed liquid may contain other components such as the dispersant described above in the "heat storage structure" section. In the mixed liquid obtained in the mixing process, the chemical heat storage material is temporarily fixed by the fibrous carbon nanostructures, and it is presumed that the heat storage structure obtained by this temporary fixation has a high porosity overall, thereby ensuring the heat storage properties and initial heat dissipation characteristics of the heat storage structure.
[0052] <<Chemical heat storage material>> As the chemical heat storage material, the chemical heat storage material described above in the section "Heat storage structure" is used. In addition, it is preferable to use a chemical heat storage material in a heat storage state, such as magnesium oxide, calcium oxide, barium oxide, Li4SiO4, etc., for preparing the mixed liquid.
[0053] <<Mixture>> In the mixing step, it is necessary to mix the dispersion liquid and the chemical heat storage material so that the mass ratio of the chemical heat storage material / fibrous carbon nanostructure is 1 or more and 20 or less, and the value of the mass ratio is preferably 3 or more, more preferably 6 or more, even more preferably 9 or more, preferably 18 or less, more preferably 16 or less, and even more preferably 14 or less. If the mass ratio of the chemical heat storage material / fibrous carbon nanostructure is less than 1, the heat storage property of the heat storage structure decreases, and if it exceeds 20, the durability of the heat storage structure is impaired. The method for mixing the dispersion liquid and the chemical heat storage material is not particularly limited, and a known mixer such as a homogenizer can be used.
[0054] <Formation process> In the forming step, the dispersion medium is removed from the mixed liquid obtained in the mixing step to form a heat storage structure. Specifically, in the forming step, the mixed liquid is filtered using a porous substrate, for example, and the filtrate obtained is dried to form the heat storage structure. The filtrate obtained by filtering the dispersion may be washed with water, alcohol, or the like before drying.
[0055] The porous substrate is not particularly limited, and examples thereof include filter paper and porous sheets made of cellulose, nitrocellulose, alumina, and the like. As the filtration method, known filtration methods such as natural filtration, reduced pressure filtration, pressure filtration, and centrifugal filtration can be used.
[0056] Furthermore, a known drying method can be used as a method for drying the filtered product.Specific examples of the drying method include hot air drying, vacuum drying, heat roll drying, infrared irradiation, etc.The drying temperature is not particularly limited, but is usually room temperature to 200°C, and the drying time is not particularly limited, but is usually 0.1 to 150 minutes. EXAMPLES
[0057] The present invention will be specifically described below based on examples, but the present invention is not limited to these examples. In each of the examples and comparative examples, various attributes and evaluations were measured or evaluated according to the following methods.
[0058] <Dispersion particle size of fibrous carbon nanostructures> The average particle size (median diameter) of the fibrous carbon nanostructures in the dispersion was measured using a laser diffraction / scattering particle size distribution analyzer (LA-960, manufactured by Horiba, Ltd.), and this value was taken as the dispersed particle size of the fibrous carbon nanostructures. <Maximum bundle diameter of fibrous carbon nanostructure> The surface of the heat storage structure was observed at a magnification of 10,000 times using a scanning electron microscope (SEM, Hitachi High-Technologies Corporation, product name "SU3500") The bundle diameter (diameter of the fiber bundle) of the observed bundle of fibrous carbon nanostructures was measured, and the largest value was taken as the maximum bundle diameter of the fibrous carbon nanostructure. <Heat storage> The heat storage structure was immersed in 300 ml of phosphoric acid aqueous solution (pH = 6.0) at 25°C for 60 minutes. The temperature of the phosphoric acid aqueous solution was continuously measured during this 60 minutes, and the maximum temperature was identified and evaluated. The higher this maximum temperature, the higher the heat storage density of the heat storage structure and the better its heat storage properties. <Initial heat dissipation characteristics> In the evaluation of the heat storage property, the temperature of the phosphoric acid aqueous solution 10 minutes after the heat storage structure was immersed in the phosphoric acid aqueous solution was recorded and used as the evaluation subject. The higher this temperature, the easier the phosphoric acid aqueous solution is impregnated into the heat storage structure and the quicker the heat dissipation is, and the better the initial heat dissipation characteristics are. <Durability> The mass M0 (g) of the heat storage structure was measured. Next, the heat storage structure was placed in 300 ml of a phosphoric acid aqueous solution (pH = 6.0) at 25°C and immersed for 60 minutes, and the immersed heat storage structure was fired at 400°C for 60 minutes in a nitrogen atmosphere. This operation was repeated five times in total, and then the mass M1 (g) of the heat storage structure was measured. From M0 and M1, the mass reduction rate of the heat storage structure = (M0-M1) / M0 x 100 (%) was calculated and evaluated according to the following criteria. The smaller the mass reduction rate, the more excellent the durability of the heat storage structure. A: Mass reduction rate is 0 mass% or more and less than 1 mass% B: Mass reduction rate is 1% by mass or more and less than 2% by mass C: Mass reduction rate is 2% by mass or more and less than 4% by mass D: The mass reduction rate was 4% or more by mass, or the durability was so low that a heat storage structure (molded body) to be evaluated could not be obtained.
[0059] Example 1 <Dispersion process> Single-walled CNTs (manufactured by Zeon Nanotechnology, product name "ZEONANO (registered trademark) SG101", SGCNT, average diameter: 3.5 nm, average length: 400 μm, BET specific surface area: 1050 m) were used as fibrous carbon nanostructures in methyl ethyl ketone as a dispersion medium so that the concentration was 0.2 wt%. 2 / g) was added and stirred with a magnetic stirrer for 1 hour to obtain a crude dispersion. Next, the above-mentioned crude dispersion was filled into a multi-stage step-down high-pressure homogenizer (manufactured by Biryu Co., Ltd., "BERYU SYSTEM PRO") having a multi-stage pressure control device (multi-stage step-down device) connected to a high-pressure dispersion processing unit (jet mill) having a capillary flow path with a diameter of 170 μm, and a pressure of 100 MPa was intermittently and momentarily applied to the crude dispersion at a temperature of 25°C and sent to the capillary flow path, which constituted one cycle. This was repeated for three cycles. Furthermore, the previous capillary flow passage was replaced with a capillary flow passage having a diameter of 90 μm, and the same dispersion treatment was carried out as one cycle. This cycle was repeated three times to obtain a dispersion liquid. The dispersed particle diameter of the fibrous carbon nanostructures in this dispersion liquid was measured. The results are shown in Table 1. <Mixing process> 4 g of magnesium oxide (Kyowa Chemical Industry Co., Ltd., "Kyowamag (registered trademark) TM150") was added as a chemical heat storage material to 200 g of the dispersion obtained in the above dispersion step, and the mixture was stirred for 2 minutes with a homogenizer to obtain a mixed liquid. The mass ratio of the chemical heat storage material / fibrous carbon nanostructure was 10. <Formation process> The total amount of the mixture (204 g) obtained in the above mixing step was filtered under reduced pressure using a Kiriyama funnel (manufactured by Kiriyama Manufacturing Co., Ltd.) as a filtering device and Kiriyama filter paper (No. 5A, diameter 3 cm) as a porous substrate to obtain a filtrate. The obtained filtrate was dried for 60 minutes in an atmosphere at a temperature of 80°C to obtain a cylindrical heat storage structure. The maximum bundle diameter, heat storage capacity, initial heat dissipation characteristics, and durability of the fibrous carbon nanostructures of this heat storage structure were measured or evaluated. The results are shown in Table 1.
[0060] Example 2 In the mixing step, the amount of magnesium oxide was changed from 4 g to 8 g, and the mass ratio of the chemical thermal storage material / fibrous carbon nanostructure was changed from 10 to 20. Except for this, the dispersion liquid, the mixed liquid, and the thermal storage structure were prepared in the same manner as in Example 1, and various measurements and evaluations were performed. The results are shown in Table 1.
[0061] Example 3 <Dispersion process> In water as a dispersion medium, single-walled CNT (manufactured by Zeon Nano Technology, product name "ZEONANO SG101", SGCNT, average diameter: 3.5 nm, average length: 400 μm, BET specific surface area: 1050 m) was used as a fibrous carbon nanostructure so that the concentration was 0.2 wt%. 2 / g) was added and stirred with a magnetic stirrer for 1 hour to obtain a crude dispersion. Next, the above-mentioned crude dispersion was filled into a multi-stage step-down high-pressure homogenizer (manufactured by Biryu Co., Ltd., "BERYU SYSTEM PRO") having a multi-stage pressure control device (multi-stage step-down device) connected to a high-pressure dispersion processing unit (jet mill) having a capillary flow path with a diameter of 90 μm, and a pressure of 100 MPa was intermittently and instantaneously applied to the crude dispersion at a temperature of 25° C., and the crude dispersion was sent into the capillary flow path, which constituted one cycle. This cycle was repeated three times to obtain a dispersion. The dispersed particle diameter of the fibrous carbon nanostructures in this dispersion was measured. The results are shown in Table 1. <Mixing process> 2 g of magnesium oxide (Kyowa Chemical Industry Co., Ltd., "Kyowamag TM150") was added as a chemical heat storage material to 200 g of the dispersion obtained in the above dispersion step, and the mixture was stirred for 2 minutes with a homogenizer to obtain a mixed liquid. The mass ratio of the chemical heat storage material / fibrous carbon nanostructure was 5. <Formation process> The total amount of the mixture (202 g) obtained in the above mixing step was filtered under reduced pressure using a Kiriyama funnel (manufactured by Kiriyama Manufacturing Co., Ltd.) as a filtering device and Kiriyama filter paper (No. 5A, diameter 3 cm) as a porous substrate to obtain a filtrate. The obtained filtrate was dried for 60 minutes in an atmosphere at a temperature of 80°C to obtain a cylindrical heat storage structure. The maximum bundle diameter, heat storage capacity, initial heat dissipation characteristics, and durability of the fibrous carbon nanostructures of this heat storage structure were measured or evaluated. The results are shown in Table 1.
[0062] Example 4 In the mixing step, the amount of magnesium oxide was changed from 2 g to 4 g, and the mass ratio of the chemical thermal storage material / fibrous carbon nanostructure was changed from 5 to 10. Except for this, the dispersion liquid, the mixed liquid, and the thermal storage structure were prepared in the same manner as in Example 3, and various measurements and evaluations were performed. The results are shown in Table 1.
[0063] Example 5 In the mixing step, the amount of magnesium oxide was changed from 2 g to 8 g, and the mass ratio of the chemical thermal storage material / fibrous carbon nanostructure was changed from 5 to 20. Except for this, the dispersion liquid, the mixed liquid, and the thermal storage structure were prepared in the same manner as in Example 3, and various measurements and evaluations were performed. The results are shown in Table 1.
[0064] Comparative Example 1 <Dispersion process> In water as a dispersion medium, single-walled CNT (manufactured by Zeon Nano Technology, product name "ZEONANO SG101", SGCNT, average diameter: 3.5 nm, average length: 400 μm, BET specific surface area: 1050 m) was used as a fibrous carbon nanostructure so that the concentration was 0.2 wt%. 2 / g) was added and stirred with a magnetic stirrer for 1 hour to obtain a crude dispersion. Next, the above-mentioned crude dispersion was filled into a multi-stage step-down high-pressure homogenizer (manufactured by Biryu Co., Ltd., "BERYU SYSTEM PRO") having a multi-stage pressure control device (multi-stage step-down device) connected to a high-pressure dispersion processing unit (jet mill) having a capillary flow path with a diameter of 170 μm, and a pressure of 100 MPa was intermittently and instantaneously applied to the crude dispersion at a temperature of 25° C., and the crude dispersion was sent into the capillary flow path, which constituted one cycle. This cycle was repeated three times to obtain a dispersion. The dispersed particle diameter of the fibrous carbon nanostructures in this dispersion was measured. The results are shown in Table 1. <Mixing process> 2 g of magnesium oxide (Kyowa Chemical Industry Co., Ltd., "Kyowamag TM150") was added as a chemical heat storage material to 200 g of the dispersion obtained in the above dispersion step, and the mixture was stirred for 2 minutes with a homogenizer to obtain a mixed liquid. The mass ratio of the chemical heat storage material / fibrous carbon nanostructure was 5. <Formation process> The total amount of the mixture (202 g) obtained in the above mixing step was subjected to reduced pressure filtration using a Kiriyama funnel (manufactured by Kiriyama Manufacturing Co., Ltd.) as a filtering device and Kiriyama filter paper (No. 5A, diameter 3 cm) as a porous substrate. However, magnesium oxide settled and water could not be removed even by suction, so a heat storage structure could not be formed.
[0065] Comparative Example 2 <Dispersion process> A dispersion liquid was obtained in the same manner as in Example 1. The dispersed particle diameter of the fibrous carbon nanostructure in this dispersion liquid was measured. The results are shown in Table 1. <Mixing process> 10 g of magnesium oxide (Kyowa Chemical Industry Co., Ltd., "Kyowamag TM150") was added as a chemical heat storage material to 200 g of the dispersion obtained in the above dispersion step, and the mixture was stirred for 2 minutes with a homogenizer to obtain a mixed liquid. The mass ratio of the chemical heat storage material / fibrous carbon nanostructure was 25. <Formation process> The entire mixture (210 g) obtained in the above mixing step was filtered under reduced pressure using a Kiriyama funnel (manufactured by Kiriyama Manufacturing Co., Ltd.) as a filtering device and Kiriyama filter paper (No. 5A, diameter 3 cm) as a porous substrate to obtain a filtrate. The obtained filtrate was dried for 60 minutes in an atmosphere at a temperature of 80°C, but the obtained heat storage structure was brittle and had poor durability, and cracked during drying. For this cracked heat storage structure, only the maximum bundle diameter of the fibrous carbon nanostructure was measured, but the heat storage property and initial heat dissipation property could not be evaluated. In addition, the durability was rated D. The results are shown in Table 1.
[0066] Comparative Example 3 In the mixing step, the amount of magnesium oxide was changed from 4 g to 0.3 g, and the mass ratio of the chemical thermal storage material / fibrous carbon nanostructure was changed from 10 to 0.75. Except for this, the dispersion liquid, the mixed liquid, and the thermal storage structure were prepared in the same manner as in Example 1, and various measurements and evaluations were performed. The results are shown in Table 1.
[0067] Comparative Example 4 <Dispersion process> The single-walled CNT was replaced with a multi-walled CNT (KUMHO PETROCHEMICAL, product name "K-NANO", MWCNT, average diameter: 13 nm, average length: 30 μm, BET specific surface area: 266 m 2 A dispersion was obtained in the same manner as in Example 1, except that the concentration of the fibrous carbon nanostructure was changed to 1 / g. The dispersed particle size of the fibrous carbon nanostructure in this dispersion was measured. The results are shown in Table 1. <Mixing process> 2 g of magnesium oxide (Kyowa Chemical Industry Co., Ltd., "Kyowamag TM150") was added as a chemical heat storage material to 200 g of the dispersion obtained in the above dispersion step, and the mixture was stirred for 2 minutes with a homogenizer to obtain a mixed liquid. The mass ratio of the chemical heat storage material / fibrous carbon nanostructure was 5. <Formation process> The total amount of the mixture (202 g) obtained in the above mixing step was filtered under reduced pressure using a Kiriyama funnel (manufactured by Kiriyama Manufacturing Co., Ltd.) as a filtering device and Kiriyama filter paper (No. 5A, diameter 3 cm) as a porous substrate to obtain a filtrate. The obtained filtrate was dried for 60 minutes in an atmosphere at a temperature of 80°C, but the obtained heat storage structure was brittle and had poor durability, and cracked during drying. For this cracked heat storage structure, only the maximum bundle diameter of the fibrous carbon nanostructure was measured, but the heat storage property and initial heat dissipation property could not be evaluated. In addition, the durability was rated D. The results are shown in Table 1.
[0068] In Table 1 below, "Mg" means magnesium hydroxide thermal storage material; "Chemical heat storage material / fibrous carbon nanostructure" means the ratio of the mass of the chemical heat storage material to the mass of the fibrous carbon nanostructure; "MEK" means methyl ethyl ketone.
[0069] [Table 1]
[0070] From Table 1, it can be seen that in Examples 1 to 5, in which a heat storage structure was produced using a fibrous carbon nanostructure having a BET specific surface area of a specified value or more, and through specified dispersion processes, mixing processes, and formation processes, in which the ratio of the mass of the chemical heat storage material to the mass of the fibrous carbon nanostructure was within a specified range, the heat storage structure exhibited excellent heat storage properties and durability. [Industrial Applicability]
[0071] According to the present invention, it is possible to provide a heat storage structure that exhibits sufficient heat storage capacity while also having excellent durability, and a method for manufacturing the same.
Claims
1. A chemical heat storage material and a fibrous carbon nanostructure are included, The BET specific surface area of the fibrous carbon nanostructure is 600 m 2 / g or more, A heat storage structure, wherein the ratio of the mass of the chemical heat storage material to the mass of the fibrous carbon nanostructure is 1 or more and 20 or less.
2. The chemical heat storage material is a magnesium hydroxide heat storage material, a calcium hydroxide heat storage material, a calcium carbonate heat storage material, a barium hydroxide heat storage material, and Li 4 SiO 4 The heat storage structure according to claim 1 , comprising at least one selected from the group consisting of heat storage materials.
3. The heat storage structure according to claim 1 , wherein the maximum bundle diameter of the fibrous carbon nanostructure is 0.2 μm or more and 0.9 μm or less.
4. Specific gravity is 0.25 g / cm 3 0.95g / cm or more 3 The heat storage structure according to claim 1 , wherein:
5. BET specific surface area is 600m 2 / g or more in a dispersion medium to prepare a dispersion liquid in which the dispersed particle diameter of the fibrous carbon nanostructure is 15 μm or more and 50 μm or less; A mixing step of mixing the dispersion liquid and the chemical heat storage material so that the ratio of the mass of the chemical heat storage material to the mass of the fibrous carbon nanostructure in the dispersion liquid is 1 to 20 to prepare a mixed liquid; a forming step of removing the dispersion medium from the mixed liquid to obtain a heat storage structure; A method for manufacturing a heat storage structure, comprising:
6. The chemical heat storage material is a magnesium hydroxide heat storage material, a calcium hydroxide heat storage material, a calcium carbonate heat storage material, a barium hydroxide heat storage material, and Li 4 SiO 4 The method for manufacturing a heat storage structure according to claim 5 , comprising at least one selected from the group consisting of heat storage materials.
Citation Information
Patent Citations
Chemical heat storage material and method for producing same
WO2019159791A1